Zakat in â€œQanunâ€ (Aceh Local Law): The Impact to Zakat Management as the Local Government Original Revenues in Baitul Mal of Aceh [Ø§Ù„Ø²ÙƒØ§Ø© ÙÙŠ "Ø§Ù„Ù‚Ø§Ù†ÙˆÙ†" (Ø§Ù„Ù†Ø¸Ø§Ù… Ø§Ù„Ù…ØÙ„ÙŠ ÙÙŠ Ø¢ØªØ´ÙŠÙ‡): ØªØ£Ø«ÙŠØ± Ø¥Ø¯Ø§Ø±Ø© Ø§Ù„Ø²ÙƒØ§Ø© ÙƒØ§Ù„Ø¥ÙŠØ±Ø§Ø¯Ø§Øª Ø§Ù„Ø£ØµÙ„ÙŠØ© Ù„Ù„ØÙƒÙˆÙ…Ø© Ø§Ù„Ù…ØÙ„ÙŠØ© ÙÙŠ Ø¨ÙŠØª Ø§Ù„Ù…Ø§Ù„ Ø§Ù„Ø¢ØªØ´ÙŠ] - Musa, Armiadi (KARSA: Journal of Social and Islamic Culture, 2018)
Zakat is considered as one of the sources of the original revenues of the local government (PAD) and is managed by Baitul Mal, whether at the level of Aceh province or at the level of the municipality and the city. It is regulated and codified in Indonesian Law No. (11) of the year 2006 regarding the Government of Aceh (UUPA) in the section of 108. The arrangement of this law has raised a number of serious problems and can be said to be a hasty and incautious movement done by Aceh government, because forcing the implementation of the governmental financial system in the mechanisms of organizing zakat and the inefficiency of the Aceh government to create special derivatives of zakat make this institution does not enjoy the independence and flexibility in organizing Zakat. The negative effects of applying this system in zakat have hampered the organization of zakat as well, especially in terms of the distribution, disbursement and efficient use of Zakat and the preparation of its reports. Employees also feel under the specter of criminalization of the designated authorities. Therefore, this research suggests that the zakat system should be set up in a special system, in a special mechanism and in a special account number. It should not be equalized with the other original revenues of the local government (PAD).